2001
DOI: 10.1023/a:1026490318131
|View full text |Cite
|
Sign up to set email alerts
|

Online Surrogate Problem Methodology for Stochastic Discrete Resource Allocation Problems

Abstract: We consider stochastic discrete optimization problems where the decision variables are non-negative integers. We propose and analyze an on-line control scheme which transforms the problem into a "surrogate" continuous optimization problem and proceeds to solve the latter using standard gradient-based approaches while simultaneously updating both actual and surrogate system states. It is shown that the solution of the original problem is recovered as an element of the discrete state neighborhood of the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…As proposed in References [3,4] the discrete functional cost defined over Y d is transformed into a 'surrogate' one that works over Y c : We construct an estimation of the gradient, according to the current measured sample path by Equations (15) and (16), and we apply a sequence of minimization steps until the optimum is reached.…”
Section: The On-line Surrogate Optimization Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…As proposed in References [3,4] the discrete functional cost defined over Y d is transformed into a 'surrogate' one that works over Y c : We construct an estimation of the gradient, according to the current measured sample path by Equations (15) and (16), and we apply a sequence of minimization steps until the optimum is reached.…”
Section: The On-line Surrogate Optimization Methodologymentioning
confidence: 99%
“…Even when the setting is deterministic and the expectation is not requested, this class of problems is NP-hard (see e.g. References [3,4] and references therein). In some cases, depending upon the form of the objective function Jðh d Þ (e.g.…”
Section: The Fading Effect and Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison with the simple SP method has shown that the cross-layer adaptive policies can yield a significant performance improvement in all quantities of interest (by reducing cell loss and call dropping, and by keeping call blocking probabilities evenly distributed among the traffic stations). Further research could be carried out along the following lines: (i) to extend the policies to stations that experience both up-and down-link fades towards multiple destinations, which create a multi-rate environment, due to the presence of different data redundancies at the same station; (ii) to investigate the effect of the adoption of on-line gradient descent techniques of the type considered in Reference [34], to relax the discrete integer optimization problem to a continuous one, whose solution can be spread over time, instead of being concentrated at the beginning of a fixed time interval (a comparison has been actually already done in Reference [35], in the presence of best-effort packet traffic only); (iii) to compare CP, CS, and hybrid allocation policies, always taking into account the presence of two basic traffic types; (iv) to include models of TCP elastic traffic and their related performance optimization (see, e.g. Reference [36]).…”
Section: Some Considerations On the Computational Timesmentioning
confidence: 99%